2022
DOI: 10.1007/s10006-022-01099-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and surgical management of pure trapdoor fracture of the orbital floor in adults: a 15-year review

Abstract: Purpose This retrospective study aims to define the optimal timing of the surgical treatment of orbital floor trapdoor fractures (OFTFs) in adults according to clinical and radiological findings. Methods From January 2006 to December 2020, 382 patients with isolated orbital floor fracture were admitted to the Division of Maxillofacial Surgery of Turin, Italy. The criteria for inclusion were age ≥ 16 years, preoperative computed tomography showing a linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
(70 reference statements)
0
4
1
Order By: Relevance
“…However, the highlight of this study is the complete absence of any significant results regarding the displacement of the rectus inferior muscle or the formation of a "trap door" by broken bony fragments. This finding is in stark contrast to the popular belief, widely assumed, that ocular mobility in patients with orbital fractures becomes impaired because of the displacement and entrapment of the rectus inferior muscle [3,19,20]. Notably, however, these beliefs, though widely held, are grounded more in common sense and anecdotal observation than on a foundation of empirical evidence derived from substantial research, as we have not found any comprehensive research paper that could prove them.…”
Section: Discussioncontrasting
confidence: 89%
“…However, the highlight of this study is the complete absence of any significant results regarding the displacement of the rectus inferior muscle or the formation of a "trap door" by broken bony fragments. This finding is in stark contrast to the popular belief, widely assumed, that ocular mobility in patients with orbital fractures becomes impaired because of the displacement and entrapment of the rectus inferior muscle [3,19,20]. Notably, however, these beliefs, though widely held, are grounded more in common sense and anecdotal observation than on a foundation of empirical evidence derived from substantial research, as we have not found any comprehensive research paper that could prove them.…”
Section: Discussioncontrasting
confidence: 89%
“…23 However, these previous reports did not disclose the presence of extraocular muscle entrapment in adult patients. 15,16,[18][19][20][21][22][23] We found 11 previously reported cases of orbital trapdoor fracture with extraocular muscle entrapment (Table 2). [4][5][6][7][8][9][10][11][12][13] The mean age of our patients combined with the previously reported patients (16 patients) was 26.1 years.…”
Section: Discussionmentioning
confidence: 93%
“…14 With regards to orbital trapdoor fracture, several previous studies have established the demographic profile and rarity of adult cases. 15,16,[18][19][20][21][22][23] Chi et al 15 examined 733 patients with orbital fracture and showed 1 adult patient (0.2%) with trapdoor fracture, while 57 other cases of orbital trapdoor fracture occurred in pediatric patients (39.6%). Parbhu et al 16 reported that 2 out of 55 adult patients had orbital trapdoor fracture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations